Infrared inhibition impacts on locally initiated and propagating action potentials and the downstream synaptic transmission - Zhu, Xuedong; Lin, Jen-Wei; Sander, Michelle Y (Neurophotonics (Print), 2020)
Significance: Systematic studies of the physiological outputs induced by infrared (IR)-mediated inhibition of motor nerves can provide guidance for therapeutic applications and offer critical insights into IR light modulation of complex neural networks. Aim: We explore the IR-mediated inhibition of action potentials (APs) that either propagate along single axons or are initiated locally and their downstream synaptic transmission responses. Approach: APs were evoked locally by two-electrode current clamp or at a distance for propagating APs. The neuromuscular transmission was recorded with intracellular electrodes in muscle cells or macro-patch pipettes on terminal bouton clusters. Results: IR light pulses completely and reversibly terminate the locally initiated APs firing at low frequencies, which leads to blocking of the synaptic transmission. However, IR light pulses only suppress but do not block the amplitude and duration of propagating APs nor locally initiated APs firing at high frequencies. Such suppressed APs do not influence the postsynaptic responses at a distance. While the suppression of AP amplitude and duration is similar for propagating and locally evoked APs, only the former exhibits a 7% to 21% increase in the maximum time derivative of the AP rising phase. Conclusions: The suppressed APs of motor axons can resume their waveforms after passing the localized IR light illumination site, leaving the muscular and synaptic responses unchanged. IR-mediated modulation on propagating and locally evoked APs should be considered as two separate models for axonal and somatic modulations.